EAST/SeSAME syndrome: Review of the literature and introduction of four new Latvian patients. Issue 1 (8th July 2018) - Celmina, M.; Micule, I.; Inashkina, I.; Audere, M.; Kuske, S.; Pereca, J.; Stavusis, J.; Pelnena, D.; Strautmanis, J.
Abstract : EAST (Epilepsy, Ataxia, Sensorineural deafness, Tubulopathy) or SeSAME (Seizures, Sensorineural deafness, Ataxia, Mental retardation, and Electrolyte imbalance) syndrome is a rare autosomal recessive syndrome first described in 2009 independently by Bockenhauer and Scholl. It is caused by mutations in KCNJ10, which encodes Kir4.1, an inwardly rectifying K + channel found in the brain, inner ear, kidney and eye. To date, 16 mutations and at least 28 patients have been reported. In this paper, we review mutations causing EAST/SeSAME syndrome, clinical manifestations in detail, and efficacy of treatment in previously reported patients. We also report a new Latvian kindred with 4 patients. In contrast to the majority of previous reports, we found a progressive course of the disorder in terms of hearing impairment and neurologic deficit. The treatment is based on antiepileptic drugs, electrolyte replacement, hearing aids and mobility devices. Future research should concentrate on recognizing the lesions in the central nervous system to evaluate new potential diagnostic criteria and on formally evaluating intellectual disability. Abstract :